Therapy of childhood acute lymphoblastic leukemia in resource-poor geospaces - Gallardo-Pérez, Moisés M.; Gale, Robert Peter; Reyes-Cisneros, Oscar A.; Sánchez-Bonilla, Daniela; Fernández-Gutiérrez, José A.; Stock, Wendy; Murrieta-Álvarez, Iván; Olivares-Gazca, Juan Carlos; Ruiz-Delgado, Guillermo J.; Fonseca, Rafael; Ruiz-Argüelles, Guillermo J. (Frontiers in Oncology, 2023)
Therapy of children with acute lymphoblastic leukaemia (ALL) in limited resource geospaces is challenging and must balance safety, efficacy, availability and affordability. We modified the control arm of the Total XI St. Jude protocol for outpatient delivery including once-weekly daunorubicin and vincristine in initial therapy, postponing intrathecal chemotherapy until day 22, prophylactic oral antibiotics/anti-mycotics, use of generic drugs and no central nervous system (CNS) radiation. Data were interrogated from 104 consecutive children ≤ 12 years (median 6 years [Interquartile Range [IQR], 3, 9 years). All therapy was given in a outpatient setting in 72 children. Median follow-up is 56 months (IQR 20, 126 months). 88 achieved a histological complete remission. Median event-free survival (EFS) is 87 months (95% Confidence Interval [CI], 39, 60). In low-risk children is 7.6 years (3.4, 8 years) whereas in high-risk children it is 2.5 years (1, 10 years). 5-year cumulative incidence of relapse (CIR) is 28% (18, 35%), 26% (14, 37%) In low-risk children and 35% (14, 52%) in high-risk children. Median survival for all subjects is not reached but must exceed 5 years. 36 children relapsed at a median of 12 months (5, 23 months). Outcomes were comparable to those reported in the control arm of the Total Therapy XI study. Average cost of the 1st 2 years of therapy was $28,500 USD compared with an average cost of about $150,000 USD in the US, an 80 percent saving. In conclusion, using an outpatient-based modification of the St. Jude Total XI protocol we obtained good results with relatively few hospitalizations or adverse events and at a substantial saving. This model can be applied in other resource poor geospaces.